Associations between 25-hydroxyvitamin D levels and pregnancy outcomes: a prospective observational study in southern China - Zhou, J; Su, L; Liu, M; Liu, Y; Cao, X; Wang, Z; Xiao, H (European journal of clinical nutrition, 2014)
Background/Objectives: Observational studies relating 25-hydroxyvitamin D (25(OH)D) and pregnancy outcomes have reported conflicting results. The aim was to assess maternal 25(OH)D status and its association with pregnancy outcomes. A prospective observational study was carried out in Guangzhou city (23 ºN), China. Subjects/Methods: Pregnant women ( n =2960) and healthy controls ( n =100) were recruited at a teaching hospital. Maternal 25(OH)D levels were measured at 16–20-week gestation. The pregnant women, if met inclusion and exclusion criteria, were enrolled in further analysis for pregnancy outcomes ( n =1953). Results: Mean serum 25(OH)D in pregnant women was 27.03±7.92 ng/ml. In total, 18.9 and 48.6% of pregnant women had low (25(OH)D less than or equal to 20 ng/ml) and medium level (25(OH)D 21–29 ng/ml) of vitamin D, respectively. 25(OH)D was highest in summer and lowest in winter, which showed a positive correlation with temperature ( R =0.942) and calcium ( R =0.074). Most maternal outcomes (premature rupture of membranes break, polyhydramnios, oligohydramnios, pre-eclampsia, cesarean section), fetal outcomes (spontaneous abortions, medically induced labor, fetal death, fetal distress, fetal growth restriction) and neonatal outcomes (malformations, birth weight and height, low birth weight, macrosomia, small-for-gestational age, score of Apgar 1′,5′, asphyxia of newborn) were not significantly different between groups, but prevalence of gestational diabetes (adjusted odds ratio (OR) 1.017; 95% confidence interval (CI) 1.002–1.033) and preterm delivery (adjusted OR 1.038; 95% CI 1.018–1.059) in high level group (25(OH)D ⩾30 ng/ml) was higher than that in low and medium level groups. Conclusions: The prevalence of low level of vitamin D (serum 25OHD ⩽20 ng/ml) was 18.9% among pregnant women in southern China. There were no significant differences in most adverse pregnancy outcomes among pregnant women with different levels of vitamin D at 16–20-week gestation except for higher prevalence of gestational diabetes and preterm delivery in women with high level of vitamin D, possibly related to the older age and higher body mass index of this group.